2017
DOI: 10.19082/4479
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support among students of medical sciences

Abstract: BackgroundSocial support is emotional and instrumental assistance from family, friends or neighbors, and has an important but different impact on individuals, mainly depending on contextual factors.ObjectiveTo determine the status of perceived social support and related personal and family characteristics of medical sciences students in Ahvaz, Iran.MethodsIn this cross-sectional study, the target population included the students of Ahvaz Jundishapur University of Medical Sciences in the second semester of 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 48 publications
3
17
0
Order By: Relevance
“…Other sources of assistance outside of the family, such as social support, are indespensabe in helping students deal with stressful events. This is supported by previous studies (Fares et al, 2016;Park et al, 2015;Silva, Cerqueira & Lima, 2014;Sreeramareddy et al, 2007;Zamani-Alavijeh et al, 2017), in which students who perceived having high levels of social support and felt satisfied with it were more likely to choose active rather than passive coping strategies to respond to stress.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Other sources of assistance outside of the family, such as social support, are indespensabe in helping students deal with stressful events. This is supported by previous studies (Fares et al, 2016;Park et al, 2015;Silva, Cerqueira & Lima, 2014;Sreeramareddy et al, 2007;Zamani-Alavijeh et al, 2017), in which students who perceived having high levels of social support and felt satisfied with it were more likely to choose active rather than passive coping strategies to respond to stress.…”
Section: Discussionsupporting
confidence: 83%
“…In terms of social support, the strategies that are applied can include maintaining positive emotions amongst students, enhancing student support activities, activating counseling services, developing peer support groups, strengthening personal coping skills by informational support, and strengthening connections or relationships between students and other school members. Moreover, by creating a network of social relationships for students, their mental well-being will also be promoted (Park et al, 2015;Zamani-Alavijeh, Dehkordi & Shahry, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 30 studies were found that adhered to the inclusion criteria set for the systematic review. Of these, 16 focused on social support and psychological outcomes (Abu-Kaf et al, 2018;Adamczyk, 2015;Bíró, Veres-Balajti, & Kósa, 2016;Ceglarek & Ward, 2016;Frison & Eggermont, 2015;Kim, Kim, & Lee, 2016;Llamas, Morgan Consoli, Hendricks, & Nguyen, 2018;Marhamah & Hamzah, 2016;Ng, Wang, & Chan, 2017;Roohafza et al, 2016;Tang & Dai, 2018;Vungkhanching, Tonsing, & Tonsing, 2016;Wang, Sun, & Wang, 2016;Wongtongkam, 2019;Yıldırım, Karaca, Cangur, Acıkgoz, & Akkus, 2017;You, Lim, & Kim, 2017); 3 focused on social support and academic achievement (Bai et al, al., 2018; Rodríguez et al, 2017); 4 focused on social support and technology use (Deechuay, Koul, Maneewan & Lerdpornkulrat, 2016;Gökçearslan, Uluyol & Şahin, 2018;Shah, Siddiqui & Ansari, 2016;; 4 focused on sources of social support (Bhochhibhoya et al, 2017;Chuah & Singh, 2016;Lee & Goldstein, 2016;Rios & Eaton, 2016); and 3 focused exclusively on gender differences in social support (Lin, 2016;Zamani-Alavijeh, Raeesi Dehkordi, & Shahry, 2017;Zhang, Zhapng, Zhang, Zhang, & Feng, 2018). All studies except one were quantitative.…”
Section: Research Resultsmentioning
confidence: 99%
“…However, data regarding social support among Pakistani healthcare students is lacking. A recent Iranian study emphasized the poor social support networks among students, reporting low social support among 60% of medical students (Zamani-Alavijeh et al, 2017). This poor social support translates into a large proportion of students with poor helpseeking skills, thus, concealing their emotional behavioural difficulties (Walter et al, 2013;Ahmed Waqas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%